IMPLEMENTATION OF LECTURE AND QUESTION-AND-ANSWER METHODS IN IMPROVING STUDENTS' LEARNING ACHIEVEMENTS IN ELEMENTARY SCHOOL - Suparlan (Journal of Education, Teaching, and Learning, 2024)
This study aims to evaluate the effectiveness of lecture and question-and-answer methods in improving the learning achievement of fourth-grade students at SD Negeri 1 Setungkep Lingsar. Employing a quantitative approach with a quasi-experimental design, the research involved two groups: an experimental group receiving instruction through lecture and question-and-answer methods, and a control group receiving conventional teaching methods. Data were collected through pre-tests and post-tests to measure students' learning achievements, along with observations and questionnaires to gather additional information on student interactions and perceptions of the teaching methods. The results indicated that the experimental group showed significant improvement in learning achievement compared to the control group. Factors influencing the effectiveness of these methods included good teacher-student interaction, active student engagement, readiness of teaching materials and media used, and positive student perceptions of the teaching methods. The implications suggest the use of lecture and question-and-answer methods as effective strategies to enhance elementary school education